The role of coaching in facilitating the transition from engineer to manager - Wallace, Esther (My University, 2016)
The extensive training that goes into developing engineering professionals is part of the price society pays for infrastructure development. Yet when it comes to developing young engineering managers, their education is often left to chance. Organisations rely on a combination of manager’s intuition and chance to recognise potential new managers and then they are expected to find their own way through the maze of policies, financial reporting, and stakeholder management politics after their appointment. This study was based in a State Owned Company where a group of new engineering managers were interviewed on their experiences as they moved into management in order to identify the challenges they experienced during the transition. The findings in the course of this research contribute to the understanding of the managerial competencies needed in a multi-cultural and multi-disciplinary engineering environment in order to guide new managers and the way in which coaching can contribute to their successful transition into engineering management. This study used a deductive approach to establish the transition challenges based on selected literature and compared the themes to the data from thematic analysis of qualitative interviews with 16 engineering professionals working in a State Owned Company engineering company. The role of new managers as talent trustees and containers of corporate memory is an essential part of skills retention strategy. This implies that dysfunctional behaviour at this level will affect future engineering skills retention and development. The cost of coaching should be offset by the risk of management failure when the new managers do not negotiate the transition challenges successfully. South African companies integrate coaching with the talent or business strategy and they use internal coaches to coach up-and-coming talent and graduates (Steenkamp, 2013). There is an urgent and important need to develop engineers into managers and therefore the assistance given to new managers would be an advantage not just in terms of the general management competencies but also the transition competencies needed in the developing countries, such as South Africa (Denton & Vloeberghs, 2003). The challenges of the transition are exacerbated by the heterogeneous nature of the business world where multiple cultures and generations complicate information exchange in the engineering labour environment. This research uses some of the insights gained from the international management competencies and applies the differences found in the South African context to identify transitionery management competencies for the developing world. The research goes on to determine how organisations and coaches can facilitate the transition of managers in South Africa.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Business Executive Coaching Wits Business School March 2015
Keywords: Executive coaching--South Africa; Employees--coaching of--South Africa; Engineering firms--Personnel management